2022
DOI: 10.1073/pnas.2200106119
|View full text |Cite
|
Sign up to set email alerts
|

A temporal gradient of cytonuclear coordination of chaperonins and chaperones during RuBisCo biogenesis in allopolyploid plants

Abstract: Ribulose-1,5-bisphosphate carboxylase/oxygenase (RuBisCo) has long been studied from many perspectives. As a multisubunit (large subunits [LSUs] and small subunits[SSUs]) protein encoded by genes residing in the chloroplast ( rbcL ) and nuclear ( rbcS ) genomes, RuBisCo also is a model for cytonuclear coevolution following allopolyploid speciation in plants. Here, we studied the genomic and transcriptional cytonuclear coordination of auxiliary chaperonin and chap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 74 publications
0
5
0
Order By: Relevance
“…Notable exceptions include Z. mays and M. sinensis, which experienced separate ancient wholegenome duplications (aWGDs) after speciation. However, to maintain the cytonuclear dosage balance, since organelle-targeting genes are prone to restore to single copy within following diploidization after aWGD [48,49], the relatively lower but significant frequency of single-copy NE-ONGs in these cases still supports the general trend (Table 1). In addition, the specialized and non-overlapping functions of species-specific NE-ONGs (Figure 3A,B) could facilitate nuclear control, fine-tuning chloroplasts and mitochondria in photosynthesis, energy supply, stress responses and even metabolism [50][51][52][53][54].…”
Section: Discussionmentioning
confidence: 63%
“…Notable exceptions include Z. mays and M. sinensis, which experienced separate ancient wholegenome duplications (aWGDs) after speciation. However, to maintain the cytonuclear dosage balance, since organelle-targeting genes are prone to restore to single copy within following diploidization after aWGD [48,49], the relatively lower but significant frequency of single-copy NE-ONGs in these cases still supports the general trend (Table 1). In addition, the specialized and non-overlapping functions of species-specific NE-ONGs (Figure 3A,B) could facilitate nuclear control, fine-tuning chloroplasts and mitochondria in photosynthesis, energy supply, stress responses and even metabolism [50][51][52][53][54].…”
Section: Discussionmentioning
confidence: 63%
“…Another intriguing feature of the process is the involvement of the nuclear‐encoded chaperonins and chaperones in the folding and assembly of the protein complexes encoded by nuclear and organelle genes. The most comprehensive overview was provided for RuBisCO (Li et al., 2022). In four different allopolyploids (wheat, cotton, tobacco, and Arabidopsis), chaperonins and chaperones of RuBisCO showed similar evolutionary genomic and transcriptomic patterns as the nuclear‐encoded gene ( rbcS ): a frequent paternal‐to‐maternal homoeologous gene conversion and maternal HEB.…”
Section: Discussionmentioning
confidence: 99%
“…Observations on RuBisCO, a single plastid-nuclear complex, provide insights into how parentspecific divergence in nuclear-encoded genes can result in preferential expression of the maternal allele, affecting its retention over time (Gong et al, 2014;Li et al, 2019Li et al, , 2020Sehrish et al, 2015). The entire process of the RuBisCO maturation involving folding and assembly stages is further complicated by the necessary involvement of nuclear-encoded chaperones and chaperonins (Li et al, 2022;Xia et al, 2020). A broad analysis of the cytonuclear accommodation in six allopolyploid lineages by Grover et al (2022) found cytonuclear genes in most lineages that are biased towards the homoeologue or the expression level from the donor of the cytoplasmic genome.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, allohexaploid wheat experienced a paternal-to-maternal gene conversion event in the region of a nuclear RbcS gene that encodes the transit peptide required for protein targeting and import into the plastids (Li et al, 2020). In addition, paternal-tomaternal gene conversions and biased expression of maternal homoeologs has been documented for some of the nuclear-encoded chaperones that function in assembly of Rubisco enzyme complexes (Li et al, 2022). Whether examples like this are driven by selection against cytonuclear incompatibilities remains unclear, but they point to a relatively unexplored area in the stabilization of allopolyploid cytonuclear interactions that merits further investigation.…”
Section: Inconsistent Genome-wide Signatures Of Selection Against Cyt...mentioning
confidence: 99%